MONOSODIUM GLUTAMATE EXPOSURE AT EARLY DEVELOPMENTAL STAGE INCREASES APOPTOSIS AND STEREOTYPIC BEHAVIOR RISKS ON ZEBRAFISH (DANIO RERIO) LARVAE - Nia Kurnianingsih; Juliyatin Putri Utami; Nurdiana Nurdiana; Diana Lyrawati (Indonesian Journal of Pharmacy, 2016)
Excessive glutamate may give neurotoxic effects and contribute to Autism spectrum disorder(ASD). In this study, we investigated prolonged exposure effects of 10 µg/mL Monosodium Glutamate (MSG) on intracellular calcium level, bax, bcl-2, ratio of bax/bcl-2 genes expression, caspase-3, apoptosis of brain cells and stereotypic behavior of Zebrafish (Danio rerio) larvae at early developmental stages. Genes expression were determined by real time PCR, caspase-3 using ELISA, intracellular Ca2+ and apoptotic cells of brain using confocal microscopy, locomotor activity by using crossing lines assay whereas stereotypic behavior by circle swimming. The results indicated that MSG exposure increased brain bax and bcl-2; and caspase-3; intracellular Ca2+; and apoptosis; stereotypic behavior; and decreased locomotor activity. Termination of MSG treatments resulted in recovery of bax, bcl-2, caspase-3 basal levels and stereotypic behavior. In conclusion, MSG exposure at early embryonic stage increased brain cell damage and risk of behavior changes.